Potential of Neem-based Varnish as Adulticide of Aedes aegypti Mosquitoes - Garza Hernandez, Javier Alfonso (2022)
Aedes aegypti (L.) (Diptera: Culicidae) is the primary vector of several arboviruses of public health importance worldwide. Resistance to insecticides led to increasing interest in exploring eco-friendly alternatives such as plant extracts used as bioinsecticides. This study describes laboratory research using neem-based varnish against adult Ae. aegypti mosquitoes. Five concentrations (0, 1, 5, 10, and 15% v/v) of neem-based varnish were evaluated against male and female Ae. aegypti by 2 hours of direct exposure. The life span of exposed Ae. aegypti mosquitoes was significantly less. LT50 ranged from 1.98-2.65 and 3.2-6.06 days for males and females, respectively, exposed to 1 to 15% concentrations of neem-based varnish. LT50 of nonexposed male and female mosquitoes were 16.20-19.60 days, respectively. The results indicated that neem-based varnish was very toxic to Ae. aegyipti mosquitoes. This botanical insecticide can be an alternative for biological control of mosquitoes.